2013
DOI: 10.1590/s0104-14282013005000022
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Payne em nanocompósitos de NBR com montmorilonita organofílica

Abstract: Resumo: Neste trabalho foi estudado o efeito Payne como uma medida das interações carga-carga e polímero-carga em nanocompósitos de montmorilonitaorganofílica (MMTorg) e borracha nitrílica (NBR), usando o Analisador de Processamento de Borracha -RPA 2000. Os nanocompósitos de NBR e MMTorg foram preparados em um misturador de rolos e o efeito Payne foi avaliado em compostos não vulcanizados tipo goma pura e contendo 5, 10, 15 e 20 phr de MMTorg. Os resultados mostraram que a composição com 5phr de MMTorg aprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(137 reference statements)
0
7
0
1
Order By: Relevance
“…It can be observed that for both properties studied, complex viscosity and minimum torque, there is increasing growth as a function of the filler content, potentialized for the 7 phr composition, meaning higher rubber-filler interaction. Beyond this formulation, that is, for 10 phr mica the viscosity increase is lower, 7 phr being possibly an indication of the filler limit content in the composition meaning better dispersion and distribution within the elastomeric matrix [23][24][25][26][27] .…”
Section: Complex Viscositymentioning
confidence: 94%
See 2 more Smart Citations
“…It can be observed that for both properties studied, complex viscosity and minimum torque, there is increasing growth as a function of the filler content, potentialized for the 7 phr composition, meaning higher rubber-filler interaction. Beyond this formulation, that is, for 10 phr mica the viscosity increase is lower, 7 phr being possibly an indication of the filler limit content in the composition meaning better dispersion and distribution within the elastomeric matrix [23][24][25][26][27] .…”
Section: Complex Viscositymentioning
confidence: 94%
“…The polymer-filler and filler-filler interactions were estimated based on the Payne Effect [23][24][25][26][27][28][29] .…”
Section: Payne Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of the modulus decrease with increasing strain amplitude by dynamic mechanical testing is commonly used to investigate the reinforcing mechanism occurring in filled rubber compounds [19][20][21] . Figure 3 shows the storage shear modulus (G') versus the strain amplitude for the co-coagulation and spray-drying experiments.…”
Section: Nitrile Rubber (Nbr) Filled Silica Productionmentioning
confidence: 99%
“…About hydrodynamic effect, the increase in modulus results from the fact that fillers form a rigid phase that cannot be deformed. As for the filler-filler interaction, known as the Payne effect, it is characterized by a modulus decrease at low strain caused by the breakdown of filler inter-aggregates [18][19][20] . For silica filled NBR compounds, it is commonly understood that filler-filler networking takes place easily due to the polarity differences between polymer and silica.…”
Section: Nitrile Rubber (Nbr) Filled Silica Productionmentioning
confidence: 99%